Autonomic Neural Circuit and Intervention for Comorbidity Anxiety and Cardiovascular Disease - Chen, Xuanzhao; Xu, Li; Li, Zeyan (Frontiers in Physiology, 2022)
Anxiety disorder is a prevalent psychiatric disease and imposes significant influence on cardiovascular disease. Numerous evidences support that anxiety contributes to the onset and progression of various cardiovascular disease through different physiologic and health behavior mechanism. However, the exact role of nuclei and neural circuit associated with anxiety disorder in cardiovascular disease is under elucidated. Several anxiety related nuclei, including amygdala, bed nucleus of stria terminalis (BNST), medial prefrontal cortex (mPFC) and hippocampus (HC), and relevant neural circuit are considered to be crucial in cardiovascular disease. And strong connection between these nuclei and autonomic nervous system have been proved. Therefore anxiety may influence cardiovascular disease through these autonomic neural circuit consisting of anxiety related nuclei and autonomic nervous system. Neuromodulation targeted these nuclei may promote the treatment of comorbid cardiovascular disease with anxiety disorders. The present review focus on the association of anxiety relevant nuclei and cardiovascular disease and discuss several non-invasive neuromodulation which may treat anxiety and cardiovascular disease